Ontological genesis and epistemological foundation of kazakh folk philosophy (Journal of Philosophy Culture and Political Science, 2018)
In recent years, increasing the relevance of the scientific interpretation of the ontological existence of the Kazakh people, its philosophy and world view through the works of folklore. Therefore, this issue has found broad support in the programs of the cultural heritage, finds its place in science. Kazakh people, who survived not a few public, social phenomenon, has a long-standing system of thinking, worldview, this show works of folklore, which is the basis of spiritual heritage. Legends, stories, poetry, a complex ideological system worthy of special studies and analysis. The revival of the philosophical ideas in the works of folklore, the creation of science-based conclusions is an actual problem. In this regard, in the depth of philosophical thought in the works of folklore becomes relevant and the nature of thought analysis. From this position, the article deals with the ontological and epistemological foundations of the genesis of the Kazakh people’s philosophy. The main approaches used in the study are the unity of historiography and logic, as well as comparative study and analysis. The results of the research show that the philosophical knowledge of folklore, based on peoples’ vision and taking into account the data, reflects the original methodological features. Folklore works that take place in the public consciousness, its origin and formation for certain purposes as a source of cultural and spiritual wealth, made it possible to analyze the cognitive nature of folklore.Key words: folklore, spirituality, philosophy, people, traditional culture, oral tradition, ethics, aesthetics.